Oesophageal adenocarcinoma and prior diagnosis of Barrett's oesophagus: a population-based study. Issue 1 (3rd April 2014) - Bhat, Shivaram K; McManus, Damian T; Coleman, Helen G; Johnston, Brian T; Cardwell, Christopher R; McMenamin, Úna; Bannon, Finian; Hicks, Blanaid; Kennedy, Grace; Gavin, Anna T; Murray, Liam J
Abstract : Objective: Endoscopic surveillance of Barrett's oesophagus (BO) provides an opportunity to detect early stage oesophageal adenocarcinoma (OAC). We sought to determine the proportion of OAC patients with a prior diagnosis of BO on a population basis and to evaluate the influence of a prior diagnosis of BO on survival, taking into account lead and length time biases. Design: A retrospective population-based study of all OAC patients in Northern Ireland between 2003 and 2008. A prior BO diagnosis was determined by linkage to the Northern Ireland BO register. Stage distribution at diagnosis and histological grade were compared between patients with and without a prior BO diagnosis. Overall survival, using Cox models, was compared between patients with and without a prior BO diagnosis. The effect of adjusting the survival differences for histological grade and estimates of lead and length time bias was assessed. Results: There were 716 OAC cases, 52 (7.3%) of whom had a prior BO diagnosis. Patients with a prior BO diagnosis had significantly lower tumour stage (44.2% vs 11.1% had stage 1 or 2 disease; p<0.001), a higher rate of surgical resection (50.0% vs 25.5%; p<0.001) and had a higher proportion of low/intermediate grade tumours (46.2% vs 26.5%; p=0.011). A prior BO diagnosis was associated with significantly better survival (HR for death 0.39; 95% CI 0.27 to 0.58), which was minimally influenced by adjustment for age, sex and tumour grade (adjusted HR 0.44; 95% CI 0.30 to 0.64). Correction for lead time bias attenuated but did not abolish the survival benefit (HR 0.65; 95% CI 0.45 to 0.95) and further adjustment for length time bias had little effect. Conclusions: The proportion of OAC patients with a prior diagnosis of BO is low; however, prior identification of BO is associated with an improvement in survival in OAC patients.